Combating Desertification: The Added Value of the Camel Farming - Faye, Bernard (Annals of Arid Zone, 2016)
The combating desertification generally involves water management, sustainable development of crops or control of land degradation. The camel, the most adapted domestic animal to desert conditions, contributes also to combat desertification. By its thirst resistance, its feeding behavior, its digestive physiology and anatomical features, it can survive in the desert region. As multipurpose animal, it allows the desert milieu to provide milk, meat, wool and power in harsh conditions, contributing to consider the desert also as a producing milieu. Moreover, the camel products like milk and meat could be valorized on local or international market. The camel farming systems in future have to integrate all these aspects not only to combat desertification, but also for a sustainable development of the desert. Key words: Camel, milk, meat, combat desertification, market.